Building spaces for participation: The dynamics of school management in professional and technological education from the perspective of an IFMG campus (Research, Society and Development, 2026)
This study examines the influence of democratic management, as established by the LDB (Law No. 9.394/96), on teacher autonomy and participation at IFMG, within the context of Professional and Technological Education (EPT). Using a qualitative and exploratory approach, semi-structured questionnaires were applied to teachers to understand their perceptions of pedagogical autonomy, engagement in collegiate bodies, and support provided by institutional management. The analysis, conducted through content analysis techniques (Bardin, 2016) and descriptive statistics, revealed that, despite the existence of formal participation mechanisms such as councils and collegiate bodies, challenges remain, including bureaucracy, centralized decision-making, and the fragility of a collaborative culture. Grounded in Libâneo (2001) and Paro (2012), the study highlights the need to strengthen democratic management as a strategy to enhance teacher responsibility and foster pedagogical innovation, proposing measures such as revising hierarchical structures and promoting critical continuing education. The study concludes that consolidating democratic practices is essential to align school management with teacher needs and EPT principles, contributing to the social quality of education.